Assessing the Effect of Bilateral Trade on Health in the Asian Region: Does Digitization Matter? - Zhang, Xinmin; Zhang, Xinqin; Yue, Xiao-Guang; Mustafa, Faisal (Frontiers in Public Health, 2022)
A recurrent theme of the literature and wider public discourse is that trade and digitization are good for health as it promotes economic prosperity. The present study investigates the impact of trade and digitization on health in 12 selected Asian economies for the period 1991 to 2019. The study applied FMOLS, and DOLS approaches for confirming the panel and economy-wise findings. The core findings of panel FMOLS confirm the significant negative impact of trade and digitization on mortality rate, but trade and digitization have significantly positively contributed to life expectancy in selected Asian countries in the long run. The study deduces some imperative policy implications related to trade, digitization, and health, specifically for Asian economies.